Handbook of self-regulation - Boekaerts, Monique; Pintrich, Paul R.; Zeider, Moshe (San Diego, Calif. : Academic Press, 2000)
The Handbook of Self-Regulation represents state-of-the-art coverage of the latest theory, research, and developments in applications of self-regulation research. Chapters are of interest to psychologists interested in the development and operation of self-regulation as well as applications to health, organizational, clinical, and educational psychology. This book pulls together theory, research, and applications in the self-regulation domain and provides broad coverage of conceptual, methodological, and treatment issues. In view of the burgeoning interest and massive research on various aspects of self-regulation, the time seems ripe for this Handbook, aimed at reflecting the current state of the field. The goal is to provide researchers, students, and clinicians in the field with substantial state-of-the-art overviews, reviews, and reflections on the conceptual and methodological issues and complexities particular to self-regulation research. Key Features * Coverage of state-of-the-art in self-regulation research from different perspectives * Application of self-regulation research to health, clinical, organizational, and educational psychology * Brings together in one volume research on self-regulation in different subdisciplines * Most comprehensive and penetrating compendium of information on self-regulation from multi-disciplinary perspectives.
Foreword. -- About the Editors. -- Contributors. -- M. Boekaerts, P.R. Pintrich, and M. Zeidner, Self-Regulation: An Introductory Overview. -- General Theories and Models of Self-Regulation: -- B.J. Zimmerman, Attaining Self-Regulation: A Social Cognitive Perspective. -- C.S. Carver and M.F. Scheier, On the Structure of Behavioral Self-Regulation. -- J.Y. Shah and A.W. Kruglanski, Aspects of Goal Networks: Implications for Self-Regulation. -- J. Kuhl, A Functional-Design Approach to Motivation and Self-Regulation: The Dynamics of Personality Systems Interactions. -- G. Matthews, V.L. Schwean, S.E. Campbell, D.H. Saklofske, and A.A.R. Mohamed, Personality, Self-Regulation, and Adaptation: A Cognitive-Social Framework. -- A. Demetriou, Organization and Development of Self-Understanding and Self-Regulation: Toward a General Theory. -- S.L. Shapiro and G.E. Schwartz, The Role of Intention in Self-Regulation: Toward Intentional Systemic Mindfulness. -- T. Jackson, J. Mackenzie, and S.E. Hobfoll, Communal Aspects of Self-Regulation. -- Domain-Specific Models and Research on Self-Regulation: -- J.B. Vancouver, Self-Regulation in Organizational Settings: A Tale of Two Paradigms. -- S. Maes and W. Gebhardt, Self-Regulation and Health Behavior: The Health Behavior Goal Model. -- S. Brownlee, H. Leventhal, and E.A. Leventhal, Regulation, Self-Regulation, and Construction of the Self in the Maintenance of Physical Health. -- M. Boekaerts and M. Niemivirta, Self-Regulated Learning: Finding a Balance Between Learning Goals and Ego-Protective Goals. -- P.R. Pintrich, The Role of Goal Orientation in Self-Regulated Learning. -- F. Rheinberg, R. Vollmeyer, and W. Rollett, Motivation and Action in Self-Regulated Learning. -- P.H. Winne and N.E. Perry, Measuring Self-Regulated Learning. -- Interventions and Applications of Self-Regulation Theory and Research: -- N.S. Endler and N.L. Kocovski, Self-Regulation and Distress in Clinical Psychology. -- T.L. Creer, Self-Management of Chronic Illness. -- D.H. Schunk and P.A. Ertmer, Self-Regulation and Academic Learning: Self-Efficacy Enhancing Interventions. -- J. Randi and L. Corno, Teacher Innovations in Self-Regulated Learning. -- E. De Corte, L. Verschaffel, and P. Op 't Eynde, Self-Regulation: A Characteristic and a Goal of Mathematics Education. -- C.E. Weinstein, J. Husman, and D.R. Dierking, Self-Regulation Interventions with a Focus on Learning Strategies. -- M. Zeidner, M. Boekaerts, and P.R. Pintrich, Self-Regulation: Directions and Challenges for Future Research. -- Index.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Self-management (Psychology); Self-control.; Learning; Goal (Psychology); Feedback (Psychology); Electronic books